The first 1,000 days of life and early childhood caries: closing the global data gap - Foláyan, Moréniké Oluwátóyìn; Gaffar, Balgis; Feldens, Carlos Alberto; Schroth, Robert J.; Ramos-Gomez, Francisco; Virtanen, Jorma I.; Lee, Hyewon; Adeniyi, Abiola; El Tantawi, Maha (Frontiers in Oral Health, 2025)
The first 1,000 days of life represent a critical window for preventing Early Childhood Caries (ECC). However, a significant global data gap obscures the true scale of ECC within this critical period. This review aims to systematically examine the global availability of ECC data for children under 36 months, discuss age-specific prevalence trends, and synthesize evidence to highlight the implications of missing data. A comprehensive analysis of a global dataset reporting ECC prevalence across 193 United Nations member states (2007–2017) was conducted. Analysis of the data was organized by the World Health Organization Region. The analysis revealed a profound data gap: 73.6% of countries had no data for children under 36 months, and only 19.7% had current data. Where data existed, rates approach or exceed 50% in some countries (e.g., Egypt: 69.6%, Mongolia: 47.5%), indicating that ECC is often well-established in the first 1,000 days of life. Significant regional disparities were identified, with the highest burden in the European Region, the Eastern Mediterranean Region, and the Western Pacific Region. Even within regions, there are extreme disparities in prevalence between countries (e.g., Kuwait at 3.0% vs. Egypt at 69.6% in the Middle East; Finland at 0.3% vs. Kazakhstan at 45.0% in Europe). The scarcity of data and high prevalence rates highlight a public oral health problem in infancy. Closing this global data gap is an essential first step to mobilize resources and implement targeted, effective prevention strategies where we can have the greatest impact.